2005
DOI: 10.1177/154405910508400903
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Mandibular Two-implant Overdentures and Conventional Dentures in the Edentulous Elderly

Abstract: Implementation of new therapies is usually governed by financial considerations, so efficacy studies should also include cost comparisons. The cost and effectiveness of mandibular conventional dentures (CD, n = 30) and two-implant overdentures (IOD, n = 30) were compared in elderly subjects. Effectiveness (Oral Health Impact Profile, OHIP-20) and cost were measured up to one year post-treatment. Data for subsequent years were estimated by the Delphi method. Using an average life expectancy of 17.9 years, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
158
0
26

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(192 citation statements)
references
References 18 publications
8
158
0
26
Order By: Relevance
“…Heydecke et al 22 reported that overdenture with two implants adds up to 56% more to the final cost when compared to conventional dentures, however , the quality of life improves by 33%. The overdenture model reported in this paper has relative technical simplicity and low cost, and it was possible to transform lower dentures into overdenture stabilized by 3 implants in one session of about an hour, improving the quality of life associated with oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Heydecke et al 22 reported that overdenture with two implants adds up to 56% more to the final cost when compared to conventional dentures, however , the quality of life improves by 33%. The overdenture model reported in this paper has relative technical simplicity and low cost, and it was possible to transform lower dentures into overdenture stabilized by 3 implants in one session of about an hour, improving the quality of life associated with oral health.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study revealed the satisfaction of the dental implant treatment and showed a positive recommendation of treatment [20][21][22][23] . A positive response to each question was similar to those of Pjetursson et al 22) and Jeong et al 23) .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] With food selection and ability to consume hard or tough food being one aspect of patient satisfaction, this study showed that there was no difference in that aspect whether patients were using conventional complete dentures or implant-retained ones. This was explained through patient predisposition to using either type of dentures; ie, patients who are ready or willing to use conventional dentures will generally have improvement in their food selection and ability to consume hard food.…”
Section: Commentarymentioning
confidence: 99%